2019
DOI: 10.3390/nu11122854
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Time-Restricted Feeding and Impact on Abdominal Obesity in Primary Care Patients: Results of a Pilot Study in a Pre–Post Design

Abstract: The epidemic of lifestyle-dependent diseases and the failure of previous interventions to combat the main causes demand an alternative approach. Abdominal obesity is associated with most of these diseases and is a good target for therapeutic and preventive measures. Time-restricted feeding (TRF) offers a low-threshold, easy-to-implement lifestyle-modification concept with promising results from animal testing. Here, we describe a pilot study of TRF with abdominally obese participants (waist-to-height ratio, WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
195
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(209 citation statements)
references
References 37 publications
9
195
1
4
Order By: Relevance
“…Total energy intake, macronutrient distribution and the number of eating occasions did not change over the four-week TRE period. Further, participants reported being adherent on 43% of days deemed non-adherent by recorded timing, suggesting previous studies using self-reporting methodology may have overestimated adherence [2,5].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Total energy intake, macronutrient distribution and the number of eating occasions did not change over the four-week TRE period. Further, participants reported being adherent on 43% of days deemed non-adherent by recorded timing, suggesting previous studies using self-reporting methodology may have overestimated adherence [2,5].…”
Section: Discussionmentioning
confidence: 90%
“…While various measures of glycaemic control have been improved in previous ad libitum and energy-matched TRE interventions of varying durations (4 days to 12 weeks), all previous investigations have been in those with normal or impaired glucose tolerance [4,5,[7][8][9]27,44,48]. Individuals with T2D have altered circadian patterns of glucose regulation [17,49], with greatest impairments to glucose tolerance in the morning compared to the evening in those with normal or impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of three non-randomized controlled trials had the moderate risks of bias [37,39] and one had the serious risk [44]. Five trials with a one group pretest-posttest design had a serious risk of bias [23,29,32,34,42].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Upon further review and quality assessment, we found 21 studies that met the topic of interest. Among the 21 studies [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], two were excluded for meta-analysis [26,27]. Their main results have been summarized in Supplementary Materials Table S3.…”
Section: Study Characteristicsmentioning
confidence: 99%